Teacher and Student’s Expectation towards Biochemistry STEM-based Module in Promoting Critical Thinking and Creativity - Novy Eurika; Suratno Suratno; Sutarto Sutarto; Jekti Prihatin (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to describe the expectations of teachers and students towards STEM-based Biochemistry modules in promoting critical thinking and creativity. An interdisciplinary approach and appropriate learning module involving elements of Science, Technology, Engineering, and Mathematics (STEM) integrated into the Engineering Design Process (EDP) are deemed to improve student learning experiences through problem-solving activities in the real world. This study used a qualitative descriptive method through a survey. The subject is teachers of Biochemistry courses and students who have taken Biochemistry courses and fill out the survey voluntarily. Research data were collected through questionnaires and analyzed using descriptive analysis. The results showed that teachers and students expect the modules need to include contextual materials and integrate the elements of Science, Technology, Engineering, and Mathematics, and the presentation of learning materials should be interactive and attractive. This research will be a reference in developing STEM-based Biochemistry teaching materials that can develop students' critical thinking skills and creativity. Â